Prognostic significance of DAPK promoter methylation in lymphoma: A meta-analysis. - Hong Wang; Lin-Yu Zhou; Ze-Bing Guan; Wen-Bin Zeng; Lan-Lan Zhou; Ya-Nan Liu; Xue-Yi Pan (PLoS ONE, 2019)
We aimed to characterize the clinical significance of epigenetic loss of death-associated protein kinase (DAPK) gene function through promoter methylation in the development and prognosis of lymphoma. PubMed, Web of Science and ProQuest databases were searched for relevant studies. Twelve studies involving 709 patients with lymphoma were identified. The prognostic value of DAPK methylation was expressed as risk ratio (RR) and its corresponding 95% confidence interval (CI), while the associations between DAPK methylation and the clinical characteristics of patients with lymphoma were expressed as odd ratios (ORs) and their corresponding 95% CIs. Meta-analysis showed that the 5-year survival rate was significantly lower in lymphoma patients with hypermethylated DAPK (RR = 0.85, 95% CI (0.73, 0.98), P = 0.025). Sensitivity analysis demonstrated consistent result. However, no associations were found between DAPK methylation and clinicopathological features of lymphoma, in relation to gender (OR = 1.07, 95% CI (0.72, 1.59), P = 0.751), age (OR = 1.01, 95% CI (0.66, 1.55), P = 0.974), international prognostic index (OR = 1.20, 95% CI (0.63, 2.27), P = 0.575), B symptoms (OR = 0.76, 95% CI (0.38, 1.51), P = 0.452), serum lactate dehydrogenase (OR = 1.13, 95% CI (0.62, 2.05), P = 0.683), and BCL-2 expression (OR = 1.55, 95% CI (0.91, 2.66), P = 0.106). Lymphoma patients with hypermethylated DAPK are at risk for poorer 5-year survival rate. DAPK methylation may serve as a negative prognostic biomarker among lymphoma patients, although it may not be associated with the progression of lymphoma.